2011
DOI: 10.1016/j.ajpath.2011.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Low-Dose UVB Inhibits CD8 T Cells and Skin Inflammation by Alternative and Novel Mechanisms

Abstract: Exposure to UVB radiation before antigen delivery at an unirradiated site inhibits functional immunological responses. Mice treated dorsally with suberythemal lowdose UVB and immunized with ova in abdominal skin generated ova-specific CD8 T cells with a significantly decreased activation, expansion, and cytotoxic activity compared with unirradiated mice. UVB also impaired the delayed-type hypersensitivity (DTH) reaction to ova. Transfer of CD4 ؉ CD25 ؉ cells from UVB-exposed mice did not suppress the ova-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…Probably, it can be explained by the fact that the dose of radiation received by patients in that study was twice lower than in our work. At the same time, there are publications about ability of UVB radiation to inhibit CD4 and CD8 cells and skin inflammation which are consistent with results of our studies regarding reduction of these cell populations in the skin of patients with vitiligo under the influence of phototherapy [30,31].…”
Section: Populations Of Cellssupporting
confidence: 81%
“…Probably, it can be explained by the fact that the dose of radiation received by patients in that study was twice lower than in our work. At the same time, there are publications about ability of UVB radiation to inhibit CD4 and CD8 cells and skin inflammation which are consistent with results of our studies regarding reduction of these cell populations in the skin of patients with vitiligo under the influence of phototherapy [30,31].…”
Section: Populations Of Cellssupporting
confidence: 81%
“…2). UVB affects CD8 + cytotoxic T lymphocyte (CTL) responses (Rana et al 2011), as well as suppressing CD4 + T helper cell (Th) type 1 (Th1) (Brown et al 1995), Th2 (McGlade et al 2007) and Th17 (Singh et al 2010) responses. UVB suppression of the T cell response is likely to be important in protection from MS because CTLs (Mars et al 2011) as well as Th1 and Th17 responses are strong drivers of CNS-targeted autoimmunity (Zamvil et al 1986;Lock et al 2002;Langrish et al 2005;Tzartos et al 2008;Yang et al 2008;Sweeney et al 2011;Inoue et al 2012).…”
Section: Cellular Mechanisms Of Uvb-induced Immune Suppressionmentioning
confidence: 99%
“…While it is now appreciated that UVB suppresses immunity in internal organs as well as the skin Rana et al 2011), the trigger must have a cutaneous origin as UVB does not penetrate deep enough to reach internal organs. Two early molecular events following UVB exposure is the release of plateletactivating factor (PAF) from keratinocytes Alappatt et al 2000) and the isomerisation of epidermal trans-urocanic acid (UCA) to cis-UCA (Anglin et al 1961;Pascher 1962).…”
Section: Platelet-activating Factor (Paf) and Serotonin (5-ht) Receptmentioning
confidence: 99%
“…In the spleen, low doses of UVB (0.5 MED; 150 mJ/cm 2 ) can inhibit the primary activation and expansion of antigen-specific CD8 T cells against protein antigens. Functionally, these cells also have impaired in vivo cytotoxic activity [35]. Using hen egg ovalbumin (OVA) as a model tumour antigen, Toda et al has shown that very high dose UVB (calculated to be about 8 MED; 2300 mJ/cm 2 ) promotes the growth of OVA-transgenic tumour cells which are rejected in unirradiated immunised mice.…”
Section: Systemic Uvb Inhibits Immune Responses In Internal Organsmentioning
confidence: 99%
“…These routes of antigen application can drain into separate lymphoid organs not directly draining the site of irradiation, and yet UVB still influences immunity within these tissues [34][35][36][37]. In the spleen, low doses of UVB (0.5 MED; 150 mJ/cm 2 ) can inhibit the primary activation and expansion of antigen-specific CD8 T cells against protein antigens.…”
Section: Systemic Uvb Inhibits Immune Responses In Internal Organsmentioning
confidence: 99%